The Gaps of Students' Writing Skills in Arabic Thesis Writing - Dinata, Rahmat Satria; Dalimunthe, Singgar Mantahari; Syafrimen, Syafrimen; Balah, Abdurrahman Assayyid Abdul Ghafar (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2023)
The relevance of the maharat al-Kitabah to an Arabic thesis writing is very significant. However, Arabic thesis writing which was also carried out by Arabic Education Study Program students created new problems, especially in aspects related to Arabic writing skills. This article aimed to reveal the gap that occurs between the ideal conditions and current conditions of students' Arabic writing skills. By using a convergent parallel mixed method design from Creswell, qualitative data was collected through FGD with 19 Arabic students at State Islamic University of Imam Bonjol who completed their studies with an Arabic thesis with 10 semesters study period or more and compared them with the quantitative data from questionnaires were distributed to 50 respondents. The gap between the ideal and the current condition of the mufrodat aspect was 98 (51%). The gap in the tarjamah aspect between ideal and current conditions was 113 (60.7%). The gap in aspects of Nahwu rules between ideal and present conditions was 78 (41.5%). The gap in aspects of Sharf  between the ideal and the current condition is 102 (54.3%). Of all the aspects studied, the biggest gap were in the tarjamah aspect. The results of the learning process analysis showed that the process was still lacking in practical aspects. For this reason, it was recommended continuing research or focusing on improving translation skills, either by conducting Classroom Action Research or Experiments with new methods that could support students' Arabic translation skills.